Implementation of Learning in Elementary Schools Is Related to the Implementation of Literacy and Numeracy Skills - Haura Sharifah; Ghullam Hamdu (Universitas PGRI Adi Buana Surabaya, 2021)
The purpose of this research to know and describe the learning process in elementary school, does the learning that has been applied in the classroom already include literacy and numeracy skills. In connection with this, a Minimum Competency Assessment will be held whose material includes literacy and numeracy competencies. The approach taken by the researcher is descriptive qualitative with 4th grade teacher participants and 4th grade elementary school students. Data was collected by means of observation, interviews, and documentation. The data analysis technique used in this study refers to the Miles and Huberman model. The results showed that teachers at SDN 2 Tuguraja Tasikmalaya and SD IT Qatrunnada Jakarta.